P–707 Does the dose or type of gonadotropin affect the reproductive outcomes of poor responders undergoing modified natural cycle IVF (MNC-IVF)?. (6th August 2021) - Drakopoulos, P; Boudry, L; Mackens, S; Vos, M. D; Verheyen, G; Tournaye, H; Blockeel, C
Abstract: Study question: Does the dose or type of gonadotropin affect the reproductive outcomes of poor responders undergoing MNC-IVF? Summary answer: Neither the type nor the dose of gonadotropins affects the reproductive outcomes of poor responders undergoing MNC-IVF. What is known already: Poor ovarian response (POR) to ovarian stimulation remains a major therapeutic challenge in routine IVF practice, because of the association with low live birth rates and high cancellation rates. Although high doses of gonadotropins are traditionally used to stimulate the ovaries in women with predicted POR, MNC-IVF has been proposed as a mild-approach alternative in this population. Typically, the MNC protocol includes GnRH-antagonists to avoid premature ovulation and gonadotropin add-back stimulation at the late follicular phase. However, evidence is sparse, and there is no consensus regarding a specific dose or type of gonadotropins in this mild stimulation protocol. Study design, size, duration: This is a retrospective cohort study including patients attending a tertiary referral University Hospital from 1st January 2017 until 1st March 2020. Participants/materials, setting, methods: All women who underwent MNC-IVF in our center were included. Gonadotropins [recombinant FSH (rFSH), urinary FSH (uFSH) or highly purified human menopausal gonadotrophin (hp-hMG)] were started when a follicle with a mean diameter of 12–14 mm was observed on ultrasound scan, followed by GnRH antagonists (0.25mg/day) from the next day onwards. Mature oocytes were inseminated using ICSI. Main results and the role of chance: In total, 484 patients undergoing 1398 cycles were included. Mean (SD) age and serum AMH were 38.2 (3.7) years and 0.46 (0.78) ng/ml, respectively. The daily dose of gonadotropins was either <75 IU/d [11/1398 (0.8%)] or 75 to < 100 IU/d [1303/1398 (93.2%)] or ≥ 100 IU/d [84/1398 (6%)]. Patients were stimulated with: rFSH [251/1398 (18%)], uFSH [45/1398 (3.2%)] or hp-hMG [1102/1398 (78.8%)]. Biochemical and clinical pregnancy rates were 142/1398 (10.1%) and 119/1398 (8.5%). Live birth was achieved in 80/1398 (5.7%) of cycles. Live birth rates (LBR) were similar between the different type and doses of gonadotropins (p-value 0.3 and 0.51, respectively). The GEE multivariate regression analysis adjusting for relevant confounders (age, BMI, number of MII oocytes) showed that the type of treatment strategy (rFSH/uFSH/hp-hMG) and the dose of gonadotropins were not significantly associated with LBR (coefficient 0.01 and –0.02, p value 0.09 and 0.3, respectively). Limitations, reasons for caution: The main limitation is the retrospective design of our study, with an inherent risk of bias. Wider implications of the findings: This is the first and largest study evaluating MNC-IVF protocol modalities. Our data demonstrate that any type of gonadotropin can be used and there is no benefit from daily doses beyond 75IU. Trial registration number: N/A